2003
DOI: 10.1098/rspb.2002.2301
|View full text |Cite
|
Sign up to set email alerts
|

Decline of North Atlantic eels: a fatal synergy?

Abstract: Panmictic species pose particular problems for conservation because their welfare can be addressed effectively only on a global scale. We recently documented by means of microsatellite analysis that the European eel (Anguilla anguilla) is not panmictic but instead shows genetic isolation by distance. In this study, we extended the analysis to the American eel (A. rostrata) by applying identical analytical procedures and statistical power. Results obtained for the American eel were in sharp contrast with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
139
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(159 citation statements)
references
References 43 publications
14
139
2
4
Order By: Relevance
“…In comparison, studies of genetic structure in other Anguilla species with a similar life history have given mixed results. Like our present results, no deviations from apparent panmixia have been found in A. rostrata (Wirth and Bernatchez, 2003), A. reinhardtii (Shen and Tzeng, 2007a) or A. japonica (Ishikawa et al, 2001; N Yoshizawa et al, in preparation; but see Tseng et al, 2006), whereas genetically distinct subpopulations have been identified in A. australis (Shen and Tzeng, 2007b), A. marmorata (Minegishi et al, 2008) and A. bicolor (Y Minegishi et al, in preparation).…”
Section: Discussionsupporting
confidence: 34%
“…In comparison, studies of genetic structure in other Anguilla species with a similar life history have given mixed results. Like our present results, no deviations from apparent panmixia have been found in A. rostrata (Wirth and Bernatchez, 2003), A. reinhardtii (Shen and Tzeng, 2007a) or A. japonica (Ishikawa et al, 2001; N Yoshizawa et al, in preparation; but see Tseng et al, 2006), whereas genetically distinct subpopulations have been identified in A. australis (Shen and Tzeng, 2007b), A. marmorata (Minegishi et al, 2008) and A. bicolor (Y Minegishi et al, in preparation).…”
Section: Discussionsupporting
confidence: 34%
“…Wirth & Bernatchez (2003) used the procedure of Beaumont (1999), which estimates several genealogical and demographic parameters from microsatellite data using Bayesian statistics, and presented values of the current effective size of the European eel stock that ranged between 1050 and 6000. These values correspond to remarkably low numbers of spawning eels that succeed in reproduction each year.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies in both species have demonstrated that they are panmictic Côté et al, 2013). Remarkably, although mitochondrial DNA lineages of the two species are reciprocally monophyletic (Avise et al, 1986), low differentation is found at microsatellite loci, with F ST values of 0.055 and 0.018 reported in previous studies (Mank and Avise, 2003;Wirth and Bernatchez, 2003).…”
Section: Introductionmentioning
confidence: 89%
“…Nevertheless, even very low gene flow between the species may be biologically significant and could explain the surprisingly low genetic differentiation between North Atlantic eels observed in previous studies (Mank and Avise, 2003;Wirth and Bernatchez, 2003). At equilibrium, F ST should be approximately equal to 1/(1 þ 4N e m) (Wright, 1931), where N e denotes effective population size and m is migration rate per generation.…”
Section: Biological Implications Of Patterns Of Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation